Empowering Indigenous Farmers with Fish Farming on South Sumatra Peatlands - Elisa Wildayana; M. Edy Armanto (HABITAT, 2021)
Forest and land fire is mentioned as a main problem of peatlands occurring every year and has provided huge losses for all parties. The research aimed how to empower indigenous farmers with fish farming on South Sumatra peatlands. This research was conducted on peatlands in Ogan Komering Ilir (OKI) District. The sampling method was using cluster technique, questionnaire and through Focus Discussion Group (FDG). All collected data were analyzed with the SPSS version 21 program and the comparisons or analyzes the relationship between the variables were also analyzed. The research results concluded that the prospect of fish farming on peatlands is very prospecful. Empowering indigenous farmers can be done through local fish farming (e.g. fishes of gabus; tebakang; sepat siam; betok; gurami and toman), and introduced fish farming (i.e. fishes of patin siam; catfish, and nila). Fish farming technology for empowering farmers can be focused on drainage and irrigation systems to maintain groundwater levels; and applying soil ameliorant (e.g. dolomite for fish ponds, lime, manure, urea and NPK fertilizer).